0061 Can using simulation improve graduate physiotherapists' clinical reasoning (measured by the critical thinking in respiratory questionnaire) and improve on-call competency?. (2nd November 2015) - Thackray, Debbie; Gough, Suzanne
Abstract : Background: On-call physiotherapy is a duty expected of all qualified physiotherapists. It is important to ensure that on-call physiotherapists are appropriately trained. It is hypothesised that simulation may be a suitable method for training post-graduate staff for on-call duties, even if respiratory is not their chosen speciality. This project is designed to evaluate the effectiveness of simulation for developing clinical reasoning, and to address the real world challenge of how to train staff and maintain competency for working in respiratory care. Methodology: mixed methods approach: A pre-post design will be used to evaluate the impact of simulation training on clinical reasoning, self-efficacy, self-confidence, and competency. Video-ethnography featuring triangulation of skills, behaviours and clinical reasoning. Participants will attend a day of simulation training and be video-recorded assessing and treating simulated patients. The participants' self-perception of their clinical reasoning and competency for on-call will be measured using the 'Critical Thinking in Respiratory Care' instrument (CTRC); 1 secondly with the ' ACPRC on-call clinical competency questionnaire ' 2 before and immediately after the training. The participants' perception of the effect of the simulation training will be measured immediately post-simulation via the ' Simulation User's Evaluation Questionnaire '. 3 The CTRC and the ACPRC questionnaires will be repeated at 6 months after the training. Analysis: Means and standard deviations will be analysed for all outcome measures. 1–3 The primary analysis will be a paired t-test of pre and immediate post-training CTRC scores to evaluate the effect of training on clinical reasoning. Participants' skills, behaviours and clinical reasoning will be compared to the scenario learning outcomes developed by expert physiotherapists and respiratory academics and triangulated with the video data to determine the effect of training. Potential impact: It is anticipated that training using simulation will improve the self-confidence and self-efficacy of on-call physiotherapists alongside performance improvements. References: Goodfellow LT, Valentine T, Holt ME. Construction and validation of an instrument to assess critical thinking in respiratory care: an empirical process. Respir Care Educ J 1999;8:13–26 Thomas S, Gough S, Broad MA, Cross J, Harden B, Ritson P, et al . On call competence: developing a tool for self-assessment. Physiotherapy 2008;94:204–211 Levett Jones T, McCoy M, Lapkin S, Noble D, Hoffman K, Dempsey J, Arthur C, Roche J. The development and psychometric testing of the satisfaction with simulation experience scale. Nurse Educ Today 2011;31(7):705–710